The Analysis of Illocutionary Act Used by the Main Character in The Nutcracker and The Four Realms Movie (2018) - Abdur Rofik; Nurfaizah Nurfaizah (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2022)
In this research, there are two problem statements. Those are: (1) What types of illocutionary act found in The Nutcracker and The Four Realms movie (2018) and (2) How illocutionary force used in each of types of illocutionary acts found in The Nutcracker and The Four Realms movie (2018). The study uses descriptive qualitative method to analyse the movie entitled “The Nutcracker and The Four Realms” produced by Mark Gordon and Larry Franco 2018 in Sweden. The collecting data of the research includes watching and reading, identifying, classifying and selecting. The analysing data of the research method by used displaying, explaining and interpreting. The researcher analyses the data using speech act and illocutionary act by the theory of Yule and Searle. The result of the study: (1) The types of illocutionary act that are used by the main character of The Nutcracker and The Four Realms. There are 10 data of assertive acts, 8 data of directive acts, 4 data of declarative acts, 6 data of expressive acts and 2 data of commissive acts. (2) Illocutionary force used in each of types of illocutionary acts found in The Nutcracker and The Four Realms, such as complaining, informing, claiming and thanking.